2022
DOI: 10.3389/fcvm.2022.819454
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitophagy in Coronary Heart Disease: Targeting the Mitochondrial Dysfunction and Inflammatory Regulation

Abstract: Coronary heart disease (CHD) is one of the main causes of death worldwide. In the past few decades, several in-depth research on the pathological mechanisms and effective treatment methods for CHD have been conducted. At present, the intervention of a variety of therapeutic drugs and treatment technologies have greatly reduced the burden on global public health. However, severe arrhythmia and myocardial fibrosis accompanying CHD in the later stages need to be addressed urgently. Mitochondria are important stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 166 publications
0
11
0
Order By: Relevance
“…Playing a central role in metabolism, mitochondria are also key players in the regulation of the immune and inflammatory responses [ 32 ]. Several studies reported the immunogenic capabilities of dysfunctional mitochondria [ 7 , 33 ].…”
Section: Mitophagy In Immunitymentioning
confidence: 99%
“…Playing a central role in metabolism, mitochondria are also key players in the regulation of the immune and inflammatory responses [ 32 ]. Several studies reported the immunogenic capabilities of dysfunctional mitochondria [ 7 , 33 ].…”
Section: Mitophagy In Immunitymentioning
confidence: 99%
“…Mitophagy prevents the accumulation of abnormal mitochondria, while the suppression of mitophagy could lead to cardiomyocyte dysfunction or even death [ 40 ]. Accumulating pieces of evidence have demonstrated that mitophagy is critically involved in the development of mitochondrial dysfunction in various settings [ 41 ]. Of note, mitochondria can repair themselves through the mitophagy system, by delivering damaged mitochondrial fragments to lysosomes, to reduce the destruction caused by mitochondrial damage to cells, including reducing oxidative stress of cells and restoring mitochondrial energy metabolism [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitophagy prevents the accumulation of abnormal mitochondria, while the suppression of mitophagy could lead to cardiomyocyte dysfunction or even death (40). Accumulating evidences have demonstrated that mitophagy is critically involved in the development of mitochondrial dysfunction in various settings (41).…”
Section: Discussionmentioning
confidence: 99%